Two syntactic positions of grammatical gender - Steriopolo, Olga (Yearbook of the Poznan Linguistic Meeting, 2018)
The paper proposes some formal and functional criteria for distinguishing between two different syntactic positions of grammatical gender: determiner gender (D-gender) and nominal gender (n-gender). Focusing on D-gender and how it differs from n-gender, this work supports previous analyses of gender as a heterogeneous category that occupies different positions in the syntactic tree. Data are presented from 27 languages, many of which are either critically endangered or already extinct.1